Structural Changes in Japanese Firms : Business Dynamism in an Aging Society - Hong, Gee Hee (IMF Working Papers; Working Paper ;, 2020)
The COVID-19 pandemic has posed a serious threat to the survival of Japanese firms, highlighting the importance of understanding how and why firms exit. In this paper, we use a rich firm-level dataset of Japanese firms to document how firm exit patterns have evolved between 2007 and 2017. Firm exit patterns have been heavily influenced by Japan's demographic trends, as a majority of exits in recent years were voluntary exits of firms (business closures) owned by CEOs aged 65 years or older without business successors. In contrast to this increase in voluntary exits, other 'traditional' firm exits (such as bankruptcies), have declined. These findings underscore the importance of addressing business transition issues in a rapidly aging society.